The gender congruency effect in sentence context depends on gender transparency and L2 proficiency: A self-paced reading study with Polish–German bilinguals - Długosz, Kamil; Olszewska, Anna (SAGE Publications, 2025)
Aims and objectives: The gender congruency effect, and so the facilitated retrieval of grammatical gender for translation equivalents of the same gender, has been documented in the recognition of isolated words in L2. Our study investigates whether this effect extends to word recognition in sentence context and whether it is modulated by gender transparency and L2 proficiency. Design/methodology/approach: Sixty late unbalanced Polish–German bilinguals completed a self-paced reading task with noun phrases manipulated for lexical gender congruency with L1 (congruent, incongruent) and noun-internal gender transparency in L2 (transparent, non-transparent). L2 proficiency was assessed through the Dialang test. Data and analysis: Reading times on the noun were analysed by means of linear mixed-effects modelling. Findings/conclusion: Results showed a gender congruency effect that was limited to transparent nouns and which was greater at lower L2 proficiency levels. Originality: The study is the first to investigate the gender congruency effect in the recognition of nouns embedded in grammatical sentences. Significance/implications: The study shows that the presence of a contextualising sentence does not eliminate the cross-language effects of grammatical gender. Furthermore, it provides first evidence that individual noun-internal gender cues modulate the gender congruency effect. The findings are discussed in terms of the relationship between gender transparency at the micro-level and the degree of activation of gender values.
Otwarte dane badawcze: https://osf.io/396hw
Keywords: gender congruency effect; gender transparency; sentence context; self-paced reading; L2 German